Comparison of three brands of round stainless steel wires used in the Begg and Tip-Edge techniques - Birkenkamp Steffen; Pancherz Hans (Sciendo, 2004)
Objective: To compare the properties of three brands of stainless steel orthodontic wires: "Bow-Flex Wire", "TP Original Wire Premier Plus" and "Australian Wire Special Plus".